Psycholinguistics A Survey of Theory and Research Problems - Sebeok, Thomas A.; Osgood, Charles E. (Indiana University Press, 1965)
The first publication of Psycholinguistics in 1954 signalled a revolution in linguistic theory. Until that time, psycholinguistics, which developed severally from language-oriented research in psychology and from psychologically-oriented research with verbal behavior in linguistics, remained on the peripheries of the established disciplines. The renewed interest and intensified cooperative work witnessed in this book resulted largely from the impact of modern science on linguistics and the questions raised by other behavioral scientists. The contributors, among them psychologists Donald E. Walker, John B. Carroll, and Kellog Wilson and linguists Sol Saporta and Leonard D. Newmark, examine the ap-proaches of the linguist, the learning theorist, and the in-formation theorist to appraise their utility for handling a variety of problems, and to discover how they can be placed in a common conceptual framework.